Using the Simcyp R Package for PBPK Simulation Workflows With the Simcyp Simulator - Anthonia M. Onasanwo; Naresh Mittapelly; Laura Shireman; Barry Vinden; Kevin McNally; James Craig; Frederic Y. Bois (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Physiologically based pharmacokinetic and pharmacodynamic (PBPK/PD) modeling aims to understand how a drug is absorbed, distributed, metabolized, excreted, and acts in a human or animal body. The Simcyp Simulator is a well‐known commercial PBPK/PD simulation software offering many options. It can, for example, use multiple compounds and population specification files to study the behavior of specific drug formulations in particular population groups. Such features can greatly speed up and optimize clinical research and drug development studies. On the other hand, the statistical coding language R offers benefits, such as easy scripting, automation, flexible statistical analyses, and visualization of results. These benefits can be applied to PBPK modeling. We describe here version 23.0.64 of an R software package that can run the Simcyp Simulator from R, changing its inputs and processing its outputs. We detail the implementation of two automated workflows for model development and verification. The first demonstrates the verification of a drug–drug interaction model for Atazanavir, an antiretroviral drug indicated for the treatment of HIV/AIDS. The second is applied to the virtual bioequivalence assessment of paliperidone palmitate long‐acting injectable suspensions. We show how simulations that could take days otherwise can be executed, analyzed, and displayed in a matter of hours.